Identification of two tandem genes associated with primary rosette branching in flowering Chinese cabbage - Guan, Jian; Li, Jinyan; Yao, Qingyu; Liu, Zhiyong; Feng, Hui; Zhang, Yun (Frontiers in Plant Science, 2022)
Branching is an important agronomic trait determining plant architecture and yield; however, the molecular mechanisms underlying branching in the stalk vegetable, flowering Chinese cabbage, remain unclear. The present study identified two tandem genes responsible for primary rosette branching in flowering Chinese cabbage by Graded Pool-Seq (GPS) combined with kompetitive Allele Specific PCR (KASP) genotyping. A 900 kb candidate region was mapped in the 28.0~28.9 Mb interval of chromosome A07 through whole-genome sequencing of three graded-pool samples from the F2 population derived by crossing the branching and non-branching lines. KASP genotyping narrowed the candidate region to 24.6 kb. Two tandem genes, BraA07g041560.3C and BraA07g041570.3C, homologous to AT1G78440 encoding GA2ox1 oxidase, were identified as the candidate genes. The BraA07g041560.3C sequence was identical between the branching and non-branching lines, but BraA07g041570.3C had a synonymous single nucleotide polymorphic (SNP) mutation in the first exon (290 bp, A to G). In addition, an ERE cis-regulatory element was absent in the promoter of BraA07g041560.3C, and an MYB cis-regulatory element in the promoter of BraA07g041570.3C in the branching line. Gibberellic acid (GA3) treatment decreased the primary rosette branch number in the branching line, indicating the significant role of GA in regulating branching in flowering Chinese cabbage. These results provide valuable information for revealing the regulatory mechanisms of branching and contributing to the breeding programs of developing high-yielding species in flowering Chinese cabbage.